The phantom of the cárcere: environmental perception in Dois Rios, Ilha Grande (RJ) - Farias, Ana Beatriz Costa; da Gama, Sonia Vidal Gomes (Geografares, 2019)
The present work has as its theme the environmental perception articulated with the concepts of cultural landscape and the historic land’s use and occupation. In the insulate territory of Ilha Grande, Angra dos Reis (RJ), point out the prison units, conservation units, and tourism activity that result in a morphodynamic singular way of the events, and are expressed in several imaginaries about the space. The objective is to analyze the relationships of this imaginary, when conveyed to the uses of travel agencies, with the perceptions of visitors in Dois Rios cove. The methodology is supported by two authors: Paulo César da Costa Gomes and Yi-Fu Tuan. The first assisting in the inventory of assets - treated as cultural landscapes and functions of tourist attractions - from the speeches used by agencies; and the second, in order to bring to Geography the feeling about the place, in the phenomenological perspective, exercising the perception of the visitors from a questionnaire focused on their ability to feel and notice through their senses, and recognize their environmental knowledge. The results presents different interpretations of the assets, and relations between the man and the attractions, pointing to a contact that, in most cases, distances itself, and in specific cases, is approaching the ideas already propagated by tourism in the insulate territory.
Keywords: Tourism; Use and Occupation; Cultural Landscape